EFEKTIVITAS PROGRAM KAMPUNG BATIK REJOMULYO SEBAGAI KAMPUNG TEMATIK DI KOTA SEMARANG - Arya Gustantya, Belvada; Widowati, Nina; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The thematic village program is one of the programs carried out by the Semarang city government to overcome environmental problems and improve the economy through poverty alleviation and active community participation. Kampung Batik Rejomulyo is one of the villages that has been able to maintain its existence since it was declared a thematic village. The method used in this research is descriptive qualitative with interview, observation and documentation data collection techniques. The indicators used to determine program effectiveness are target accuracy, program outreach, program objectives, and program monitoring. In addition, the driving and inhibiting factors for the program are seen from environmental conditions, inter-organizational relationships, organizational resources for program implementation, and the characteristics and capabilities of implementing agents. The results of the research show that the implementation of the thematic village program in Kampung Batik Rejomulyo cannot be said to be fully effective because there are still people who do not understand the aims and objectives of the program, improving the quality of the economy, environment and community participation is not yet optimal and program monitoring has not provided real changes to the community. Program inhibiting factors come from environmental conditions, inter-organizational relationships, organizational resources, and the ability of program implementers. Suggestions that can be given by the author to optimize the effectiveness of the program are the need to carry out intensive socialization using appropriate media for the community, strengthening cooperation between related parties to innovate in developing batik villages, mutual cooperation between communities to protect the environment and infrastructure as well as evaluation in carry out program supervision. Factors inhibiting the program can be overcome by making innovations in developing batik businesses, strengthening batik associations and coordinating and communicating between stakeholders.